2014
DOI: 10.1016/j.bbamem.2013.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Membrane interactions and biological activity of antimicrobial peptides from Australian scorpion

Abstract: UyCT peptides are antimicrobial peptides isolated from the venom of the Australian scorpion. The activity of the UyCT peptides against Gram positive and Gram negative bacteria and red blood cells was determined. The membrane interactions of these peptides were evaluated by dye release (DR) of the fluorophore calcein from liposomes and isothermal titration calorimetry (ITC); and their secondary structure was determined by circular dichroism (CD). Three different lipid systems were used to mimic red blood cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 35 publications
1
25
0
1
Order By: Relevance
“…The observed insecticidal and antibacterial activities of scorpion AMPs against A. pisum and its bacterial symbionts are supported by earlier research in which indolicidin, an AMP from bovine neutrophils, showed activity against the green peach aphid Myzus persicae (Sulzer) and also affected the bacteriome [ 50 ]. Furthermore, scorpion AMPs (UyCT3, UyCT5, Uy192, Um4, D11) and indolicin showed activity against Escherichia coli , which is closely related to B. aphidicola , providing further support for our observations [ 20 , 21 , 28 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The observed insecticidal and antibacterial activities of scorpion AMPs against A. pisum and its bacterial symbionts are supported by earlier research in which indolicidin, an AMP from bovine neutrophils, showed activity against the green peach aphid Myzus persicae (Sulzer) and also affected the bacteriome [ 50 ]. Furthermore, scorpion AMPs (UyCT3, UyCT5, Uy192, Um4, D11) and indolicin showed activity against Escherichia coli , which is closely related to B. aphidicola , providing further support for our observations [ 20 , 21 , 28 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 81%
“…We selected AMPs from two Australian scorpion species ( U. yaschenkoi and U. manicatus ) because the evolution of scorpions has involved the development of venom glands producing peptides and proteins that can efficiently kill insect prey [ 24 , 26 ]. Certain scorpion AMPs are also active against human pathogenic bacteria [ 21 , 28 ]. We used three insect AMPs (cecropin A, apidaecin and stomoxyn), as well as a synthetic insecticide (imidacloprid) and antibiotic (rifampicin) as controls to evaluate the scorpion AMPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the overall DPP-IV inhibitory effect seen in food protein hydrolysates originates from a mixture of peptides rather than a single peptide. The isobole methodology has been mainly utilised to study interactive effects between 75 drugs, fertilisers, pesticides and phytochemicals 13 with a limited number of examples applied to antimicrobial peptide mixtures 20,21 . An additive effect of Sitagliptin (when studied at one level) and peptide mixtures on DPP-IV inhibitory properties has previously been shown 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the relationship between AMP structure and its mode of action and knowing the specific process for AMP action are vital for the design of new antibiotic peptides. To understand their mode of action, the interaction of AMPs have been studied with Gram‐negative Escherichia coli , Gram‐positive S. aureus and Bacillus subtilis , and human red blood cells (RBCs) in vivo and in vitro …”
Section: Introductionmentioning
confidence: 99%